2021
DOI: 10.3389/fpsyt.2021.595979
|View full text |Cite
|
Sign up to set email alerts
|

Faith-Based Coping Among Arabic-Speaking Refugees Seeking Mental Health Services in Berlin, Germany: An Exploratory Qualitative Study

Abstract: Background: The benefits of faith-based coping or using religious and spiritual beliefs as a stabilizing force for interpreting stressful or distressing events are largely unexplored among the exodus of Arabic-speaking refugee populations from Muslim-majority countries, particularly those resettled in Europe. The present study aimed to explore the manifestation of faith-based coping strategies among Arabic-speaking refugee adults seeking mental healthcare services in Berlin, Germany and explore how favorable f… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 26 publications
1
9
0
1
Order By: Relevance
“…Such individuals may benefit less from refugee integration or not be interested in it at all. Nevertheless, by using that kind of spiritual assessment, counselling can assess patients for unmet religious and spiritual needs, coping methods and can use interventions to deepen meaning-making within the counsellor–client relationship [ 24 , 93 ]. While health professionals can effectively identify the religious and spiritual needs of refugees, meeting these needs may require the involvement of priests and imams of the relevant religious denominations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Such individuals may benefit less from refugee integration or not be interested in it at all. Nevertheless, by using that kind of spiritual assessment, counselling can assess patients for unmet religious and spiritual needs, coping methods and can use interventions to deepen meaning-making within the counsellor–client relationship [ 24 , 93 ]. While health professionals can effectively identify the religious and spiritual needs of refugees, meeting these needs may require the involvement of priests and imams of the relevant religious denominations.…”
Section: Discussionmentioning
confidence: 99%
“…These could be complex and intersect with various individual, social and structural conditions [ 22 , 23 ]. Moreover, preliminary research findings suggest that religion and faith practices play an essential role in the mental health and integration of refugees in Germany, which provides insight into how mental health care can be provided in a religion-sensitive manner that offers alternatives to the social, cultural and linguistic barriers of the German health care system [ 24 ]. Ano and Vasconcelles [ 25 ] conducted a meta-analysis to integrate research on religious coping with adaptation to stressful events.…”
Section: Introductionmentioning
confidence: 99%
“…A total of 37 articles were included in the analysis ( Figure 1 ) [ 6 , 7 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ]. Results were categorized as “public health interventions”, where interventions were related to addressing public health needs across various topics including mental health and physical activity, then “vaccination interventions” which are those focused specifically on supporting vaccine uptake.…”
Section: Resultsmentioning
confidence: 99%
“…Other studies have shown that FBOs provide their members with various coping strategies to address mental health barriers such as prayer, scripture, social support groups, religious services, and aid from religious leaders, showing a potential opportunity for other health-related dialogue such as vaccination. Rayes et al [ 31 ] performed qualitative interviews on Arabic-speaking refugee populations from Muslim majority countries resettling in Europe. The study found that participants with a stronger devotion to faith were more likely to use faith-based coping mechanisms when handling challenges and seeking mental health services.…”
Section: Resultsmentioning
confidence: 99%
“…Eine andere Studie zu arabischstämmigen Geflüchteten in Deutschland arbeitet heraus, wie sich deren Glaube und religiöse Praxis während und nach der Flucht auf ihre psychische Gesundheit auswirkt, die durch die Fluchterfahrung einer hohen Belastung ausgesetzt wird (Rayes et al, 2021). Hier wird etwa deutlich, wie wichtig kultur-und glaubensspezifische Interpretationen von psychischen Schwierigkeiten auch für Bewältigungsstrategien sind.…”
Section: Religion Als Ressource Für Geflüchteteunclassified